Impact of COVID-19 lockdown on physical activity and psychological well-being in taekwondo athletes - Quintero, A. M.; Ojeda-Aravena, A.; Arc-Chagnaud, C.; Quintero, J. M. G.; De la Rosa, A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. Coronavirus disease 2019" (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coro- navirus 2 (SARS-CoV-2). Problem and Aim. investigate the effects of lockdown on the physical activity and psychological well-being of Colombian taek- wondo athletes during the COVID-19 outbreak. Methods. A total of 114 athletes (male = 78; female = 36) were surveyed. Athletes responded to an online survey - the Interna- tional Physical Activity (PA) Questionnaire and the psychological General Well-Being Index, considering "before" and "during" the pandemic. Results. Lockdown had a negative effect on total PA levels (MET-min/week) (F = 20.16; p < 0.01), with females displaying the greatest decrease (from 5.420 to 3.403; p < 0.05). In the total sample, a greater change in PA behavior between before and dur- ing confinement was observed in highly active participants (n = 93 vs n = 63) as total MET-min/week (6.121vs 5.556; p < 0.05). Assessment of psychological well-being revealed significant differences by gender, with females being more affected by lockdown in perceived anxiety (p < 0.05), vitality (p < 0.01) and general health (p<0.01). However, no differences were found at technical level. PA levels during lockdown revealed significant inter-group differences between the moderate and high-activity male groups for anxiety (p<0.01) and vitality (p < 0.05), while the moderate and high-active female groups showed differences in the self-con- trol (p < 0.05) and well-being (p < 0.05) dimensions. Conclusions. while COVID-19-associated restrictions were essential to preserve public health, PA and psychological well-being were compromised, affecting mainly female taekwondo practitioners.